Complementary and alternative medicines chosen for specific health problems: Internet survey using the I-CAM-Q in Japan: A STROBE-compliant cross-sectional study. Issue 41 (14th October 2022) - Tabata, Ryo; Yamaguchi, Harutaka; Ookura, Yoshihiro; Tani, Kenji
Abstract : This study investigated the different complementary and alternative medicines (CAMs) adopted by people in Japan, as well as the health problems treated with CAMs. Understanding more about this topic will facilitate the appropriate incorporation of CAMs into conventional medicine when treating health problems. Data were collected through an online survey based on the International Questionnaire to Measure Use of Complementary and Alternative Medicine (I-CAM-Q). The study examined CAM utilization among people aged 20 years or older; 164 valid responses were collected (18.9%). We adopted a cross-sectional design. We then compared the relationships between the specific health problems reported by participants, their self-help practices, and the kinds of healthcare specialists consulted. We also examined participants' reasons for using CAMs and their responses regarding the usefulness of the CAMs adopted. We found that self-help/CAM practices differed for specific health problems. Participants with musculoskeletal and heart problems were more likely to use poultices. Those with respiratory and digestive problems were more likely to practice yoga, tai chi, and qigong. Those with digestive and neurological problems were more likely to use aromatherapy. The I-CAM-Q questionnaire also revealed the purpose and usefulness of the CAMs utilized as well as the participants' attitudes regarding conventional medicine. The study showed that participants find physicians less helpful than other options for treating their health problems. Additionally, when asked whether it was helpful to consult with a specific professional for health problems, there was a higher percentage of participants who answered "Very helpful" for professionals, like massage, judo, acupuncture, and moxibustion therapists, than for physicians. The results of this study will help to inform medical providers of the most appropriate types of CAMs for dealing with various health problems.